Hubungan Tingkat Stres dengan Status Gizi Mahasiswa Tingkat Akhir S1 Fakultas Ilmu Keperawatan Unissula - Nurul Puspita Anggraeni; Nutrisia Nu'im Haiya; Moch. Aspihan (Journal of Health, Medical, and Psychological Studies, 2026)
Final-year students are vulnerable to academic stress due to the demands of completing their thesis. Unmanaged stress can affect eating patterns and lead to changes in nutritional status. This study aimed to determine the relationship between stress levels and nutritional status among final-year undergraduate nursing students at Sultan Agung Islamic University (UNISSULA). This study employed a quantitative research design with a cross-sectional approach. A total of 138 final-year students were selected using purposive sampling. Stress levels were measured using the Perceived Stress Scale (PSS-10), while nutritional status was assessed using the Body Mass Index (BMI). Data were analyzed using univariate and bivariate analysis with the Gamma test. The results showed that most respondents experienced very severe stress (71.74%) and had normal nutritional status (47.83%). The Gamma test revealed a p-value of 0.003 (p < 0.05) with a correlation coefficient of 0.429, indicating a significant relationship with moderate strength between stress levels and nutritional status. Conclusion there is a significant relationship between stress levels and nutritional status among final-year undergraduate nursing students at UNISSULA. Effective stress management is essential to maintain optimal nutritional status and overall health.